Burnout Sebagai Mediator Dalam Pengaruh Beban Kerja Terhadap Kinerja Karyawan - Abell Abell; Eka Mariyanti; Rasidah Nasrah (CV. ITTC INDONESIA, 2024)
This study aims to determine the effect of workload on employee performance with burnout as a mediating variable in employees of Bank Nagari Pasar Raya Branch Padang. Workload is often considered a factor that affects employee performance, while burnout can arise as a result of excessive workload and impact performance. This study uses a quantitative approach with data analysis using the Partial Least Square (PLS) 4.0 method to test the relationship between workload, burnout, and employee performance variables. The results of the analysis show that workload has a positive and significant influence on employee performance at Bank Nagari Pasar Raya Padang Branch. This means that, as workload increases, employee performance also increases. However, the results also reveal that burnout does not serve as a mediating variable in the relationship between workload and employee performance. This is due to the promising compensation provided by Bank Nagari Pasar Raya Padang Branch to its employees, which allows employees to manage work stress more effectively and prevent burnout that affects their performance. Thus, adequate compensation and good stress management can reduce the negative impact of high workload on burnout and employee performance. These findings provide important insights for human resource management in the banking industry, especially in designing workload and compensation policies that can maximize employee performance without causing burnout.